Relationship between learning strategies and the academic performance of Colombian student (Encuentros, 2016)
The focus of research is the study of learning strategies and academic achievement in students of primary education public institution Policarpa Salavarrieta. As a non-experimental methodology selective ex post-facto design or assumed, because the participants were selected according to their personal characteristics and a relationship between the variables under study were established: learning strategies (VI) and academic performance (VD); picking a purposive sample of 60 Grade 5 students who responded to the application of the ACRA Scale ROMÁN AND GALLEGO (1994). The analyzes were descriptive of the main study variables and linear correlations between learning strategies and academic performance. The results showed statistically significant correlations between different scales of ACRA Test being all positive, just as it can be seen that subjects such as Spanish Language and Natural Sciences have a strong association. Finally it was concluded that the association between the variables of learning strategies and academic performance, so it can be stated that the appropriate use of learning strategies depend on the scope of academic performance.Keywords: Acquisition Support, Coding, Recovery, Performance